PERBANDINGAN DISABILITAS PENDERITA MIGREN YANG TERJADI DI DALAM DAN DI LUAR PERIODE MENSTURASI - Christianty Hasfiany Girsang*, Khairul Putra Surbakti*, Hasan Sjahrir* (NEURONA, 2011)
INTRODUCTION MIGRAINE ATTACK IS A UNILATERAL HEADACHE ATTACK USUALLY ASSOCIATED WITH ANOREXIA AND SOMETIMES WITH NAUSEA AND VOMITING NOWADAYS MIGRAINE IS THE 19TH WORLDWIDE RANK OF ALL DISEASES WHICH IS CAUSE DISABILITY PREVIOUS STUDIES SHOWED THAT FEMALE WHO HAS MIGRAINE TENDED TO BE MORE SLIGHTLY DISABLED